Williams syndrome presenting with findings consistent with Alagille syndrome. Issue 1 (7th November 2014) - Sakhuja, Pankaj; Whyte, Hilary; Kamath, Binita; Martin, Nicole; Chitayat, David
Key Clinical Message Conjugated hyperbilirubinemia, posterior embryotoxon, and vertebral anomalies are not features of William syndrome (WS). We herein report a preterm infant who presented with features suggestive of Alagille syndrome, but microarray showed findings consistent with WS. This further extends the phenotype of WS and emphasizes the need for microarray analysis.